2021
DOI: 10.1111/maps.13661
|View full text |Cite
|
Sign up to set email alerts
|

Extraterrestrial hydroxy amino acids in CM and CR carbonaceous chondrites

Abstract: The abundances, distributions, and enantiomeric ratios of a family of three‐ and four‐carbon hydroxy amino acids (HAAs) were investigated in extracts of five CM and four CR carbonaceous chondrites by gas chromatography‐mass spectrometry analyses. HAAs were detected in both the acid hydrolysates of the hot water extracts and the 6 M HCl extracts of all the CM and CR chondrites analyzed here with total hot water and HCl extractable HAA concentrations ranging from 6.94 to 315 nmol g−1. The HAA analyses performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Various amino acids were identified, including glycine, alanine, β-alanine, and C 3 and C 4 hydroxy amino acids (HAAs) [hydroxyl (−OH) group-bearing amino acids] with α-, β-, and γ-structural isomers. Although the distribution of HAAs in carbonaceous chondrites has received little attention except for proteinogenic amino acids serine and threonine, we previously detected a family of α-, β-, and γ-HAAs in various CM and CR chondrites. , The ubiquity of α-, β-, and γ-HAAs in carbonaceous chondrites suggests that a similar mechanism as in our experiments using aldehydes and ammonia could have proceeded in the meteorite parent bodies.…”
Section: Introductionsupporting
confidence: 73%
See 4 more Smart Citations
“…Various amino acids were identified, including glycine, alanine, β-alanine, and C 3 and C 4 hydroxy amino acids (HAAs) [hydroxyl (−OH) group-bearing amino acids] with α-, β-, and γ-structural isomers. Although the distribution of HAAs in carbonaceous chondrites has received little attention except for proteinogenic amino acids serine and threonine, we previously detected a family of α-, β-, and γ-HAAs in various CM and CR chondrites. , The ubiquity of α-, β-, and γ-HAAs in carbonaceous chondrites suggests that a similar mechanism as in our experiments using aldehydes and ammonia could have proceeded in the meteorite parent bodies.…”
Section: Introductionsupporting
confidence: 73%
“…In the same manner, isoserine (β-HAA) or 4-A-2-HBA (γ-HAA) may also form from the reaction of ammonia with 2-hydroxy-3-oxopropanoic acid (β-oxoacid) or 2-hydroxy-4-oxobutanoic acid (γ-oxoacid), respectively (Figure ). Therefore, the reaction between oxoacids and ammonia can be hypothesized to produce various amino acids, including the α-, β-, and γ-HAAs found in CM and CR carbonaceous chondrites. , Note that the hydrolysis experiment of N -oxalylglycine demonstrated that the precursor compound gradually hydrolyzes at 60 °C. In the case of organic reactions in meteorite parent bodies, N -oxalylglycine and similar precursor compounds (Figure ) are likely to hydrolyze completely to form amino acids after prolonged aqueous alteration (e.g., 5–20 Myr) in meteorite parent bodies .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations